The seismic vulnerability of buildings in the central zone of Peru through the application of the rapid visual detection method - Madyori Gabriela, Felix Gutierrez (2023)
In order to predict the occurrence of major earthquakes, the world scientific community carried out the World Seismicity Map, establishing the most seismic zone known as the Pacific Ring of Fire, where Peru is included, as a result of the earthquakes that have occurred and that have led to structural damage to buildings and loss of human lives throughout the history of disasters in the country. The city of Chupuro is located in the central zone of Peru, categorized as a level III seismic zone, which makes it susceptible to seismic events. That is why the purpose was to determine the seismic vulnerability in 226 buildings in the city of Chupuro that were analyzed using the rapid visual detection method (RVS), with the use of the data collection sheet stipulated by the FEMA P-154 methodology, which is quite conservative and is based mainly on the category, structural system, soil and topography, providing a quick evaluation in any type of building and place. The field investigation identified the buildings according to the number of floors, type of construction, year of construction, irregularities in floor plan and height; they showed that 61% of the buildings are immersed to suffer seismic damage and hazards. In addition, these buildings showed that they are prone to suffer grade 2 (moderate damage) and grade 3 (severe damage) damage, mostly comprised of masonry buildings of medium height. It is concluded that there is a clear probability that the damage state of the buildings is 53.1% Grade 2 and 27.0% Grade 3 leading to moderate and severe damage respectively. Finally, with this we want to initiate actions to follow in order to achieve a country less vulnerable to seismic events with adequate management policies that include the population and authorities.